Analisis Hukum Perpajakan terhadap Investasi Properti Terkait dengan Penerimaan Pajak di Kota Medan - Budiman, Syarioto; Ginting, Budiman; Maharani, Utary; Lubis, Anggreni Atmei (Universitas Medan Area, 2020)
The method used in this research is normative juridical approach is prescriptive to examine the sources of literature relevant to the theme of research, including research on the general principles of law, legislation, as well as provisions on the cash receipts from the tax sector property. Implementation of the UN tax collection and BPHTB include data collection, assessment, determination, administration and comprehensive services, of course this is not easy and has many obstacles. The obstacles encountered in the area of property tax collection comes from internal and external side. In terms of internal investment required a high cost in the provision of facilities, shortage of human resources in collecting taxes, updating the data base, while in terms of the external is the awareness of the community in paying taxes, their mode of misappropriation of law and the administration of the taxpayer, as well as the role ofÂ notary still less than the maximum help in the collection of property taxes.